Crystal structure of Rv1220c, a SAM‐dependent O‐methyltransferase from Mycobacterium tuberculosis. Issue 6 (1st June 2017) - Yan, Qiaoling; Shaw, Neil; Qian, Lanfang; Jiang, Dunquan
Abstract : The crystal structure of Rv1220c reveals a typical methyltransferase fold and a His164–Asp138 pair which is conserved in homologues from all species of Mycobacterium . Abstract : Rv1220c from Mycobacterium tuberculosis is annotated as an O ‐methyltransferase ( Mtb OMT). Currently, no structural information is available for this protein. Here, the crystal structure of Mtb OMT refined to 2.0 Å resolution is described. The structure reveals the presence of a methyltransferase fold and shows clear electron density for one molecule of S ‐adenosylmethionine (SAM), which was apparently bound by the protein during its production in Escherichia coli . Although the overall structure of Mtb OMT resembles the structures of O ‐methyltransferases from Cornybacterium glutamicum, Coxiella burnetti and Alfa alfa, differences are observed in the residues that make up the active site. Notably, substitution of Asp by His164 seems to abrogate metal binding by Mtb OMT. A putative catalytic His–Asp pair located in the vicinity of SAM is absolutely conserved in Mtb OMT homologues from all species of Mycobacterium, suggesting a conserved function for this protein.